Early cellular responses of germ-free and specific-pathogen-free mice to Francisella tularensis infection - Krocova, Zuzana; Plzakova, Lenka; Benuchova, Milota; Macela, Ales; Kubelkova, Klara (Microbial pathogenesis, 2018)
Bacteria that are highly virulent, expressing high infectivity, and able to survive nebulization, pose great risk to the human population. One of these is Francisella tularensis, the etiological agent of tularemia. F. tularensis is a subject of intense scientific interest due to the fact that vaccines for its immunoprophylaxis in humans are not yet routinely available. One of the substantial obstacles in developing such vaccines is our insufficient knowledge of processes that initiate and regulate the expression of effective protective immunity against intracellular bacteria. Here, we present data documenting the different pattern of cellular behavior occurring in an environment unaffected by microbiota using the model of germ-free mice mono-associated with F. tularensis subsp. holarctica strain LVS in comparison with a classic specific-pathogen-free murine model during early stages of infection.
Keywords: slezina; přirozená imunita; Germ-Free Life; modely nemocí na zvířatech; Peritoneum; cytokiny; Mice, Inbred BALB C; Mice; organismy bez specifických patogenů; myši inbrední BALB C; zvířata; Cytokines; interakce hostitele a patogenu; Disease Models, Animal; bakteriální vakcíny; Bacterial Vaccines; tularemie; mikrobiota; Spleen; Tularemia; Specific Pathogen-Free Organisms; gnotobiologické modely; peritoneum; myši; ženské pohlaví; Immunity, Innate; Animals; Host-Pathogen Interactions; Francisella tularensis; Microbiota; Female